Validitas Model Pembelajaran BATU OBSIDIANKO (Baca, Tulis, Observasi, Diskusi, Analisis, Komunikasi) untuk Pembelajaran IPA SMP - Sri Sugiarti; Indrawati Indrawati; Nuriman Nuriman (Jurnal Pembelajaran dan Pendidikan Sains, 2017)
The aim of the study is to describe the validity of learning model of batu obsidianko for learning science of junior high school. The kind of research in descriptive. Subject of the study is student class VIII SMPN 2 Genteng odd semester 2016-2017 academic year. Technique to collect the data is questionair sheet for meaning validity of the model. Data is analized descriptively by using percentage. Finding of the research is the score validity of the model is 82,57% in average of expert validators. The average validity of user (teachers) is 83,33%. Both of the validators give score validity in very valid category. In conclussion the model of batu obsidianko is very valid for learning of science students class VIII SMPN 2 Genteng Banyuwangi. Keywords: science learning, learning model, validity of learning model